A Long-Term Follow-up Study of Asthmatic Children Discontinued Allergen-Specific Immunotherapy - Huang, Yana; Huang, Ying; Li, Jie; Zhang, Benjin (Journal of Child Science, 2024)
Our objective was to explore the factors associated with the prognosis of allergic asthmatic children with poor compliance with subcutaneous immunotherapy (SCIT). A telephonic follow-up was conducted in 616 asthmatic children who received SCIT treatment from June 2005 to October 2010. The status of asthmatic controlled was based on their level of asthma symptom control when they were followed-up. Seven factors, including sex, age, family history of allergic disease, severity of mite allergy, times of SCIT, whether inhaled corticosteroids regularly, and with rhinitis or not, were analyzed. In total, 322 asthmatic children discontinued the 3-year course of SCIT. Of the 127 children included in the final analysis, 85 (66.9%) were asthmatic controlled patients and 42 (33.1%) were asthmatic uncontrolled patients. The median (interquartile range) age of the 127 asthmatic children was 7.1 ± 4.8 years. The proportion of male and female was 87/40. In the seven factors, family history of allergic diseases (p = 0.035), whether inhaling corticosteroids regularly (p = 0.007), were significantly related to the level of asthma symptom control, whereas the age of these asthmatic children, severity of mite allergy, times of SCIT, and asthma with rhinitis or not had no relation to the level of asthma symptom control. Our findings revealed that the family history of allergic diseases was an important factor affecting the prognosis of childhood asthma, and inhaling corticosteroids regularly after discontinuing SCIT could significantly improve their prognosis. These results could provide value in clinical asthma treatment.
Keywords: asthma; subcutaneous immunotherapy; compliance; follow-up; risk factors